Exploring a Role for Flow-Induced Aggregation Assays in Platform Formulation Optimisation for Antibody-Based Proteins - Willis, Leon F.; Toprani, Vishal; Wijetunge, Sashini; Sievers, Annette; Lin, Laura; Williams, Jeanine; Crowley, Tom J.; Radford, Sheena E.; Kapur, Nikil; Brockwell, David J. (Journal of pharmaceutical sciences, 2024)
•Therapeutic proteins are exposed to the effects of fluid flow (hydrodynamic forces and interfaces) throughout their lifetimes, which could cause aggregation.•A bespoke Extensional Flow Device (EFD) and orbital shaking are used to evaluate aggregation propensity of antibodies and fusion proteins in platform formulations.•The EFD identifies robust molecules and distinguishes between formulations, using milligram quantities of material.•The optimised formulation conditions can be used to protect sensitive, novel Fc-fusion proteins, aiding the manufacture of future molecules. The development time of therapeutic monoclonal antibodies (mAbs) has been shortened by formulation platforms and the assessment of ‘protein stability’ using ‘developability’ assays. A range of assays are used to measure stability to a variety of stresses, including forces induced by hydrodynamic flow. We have previously developed a low-volume Extensional Flow Device (EFD) which subjects proteins to defined fluid flow fields in the presence of glass interfaces and used it to identify robust candidate sequences. Here, we study the aggregation of mAbs and Fc-fusion proteins using the EFD and orbital shaking under different formulations, investigating the relationship between these assays and evaluating their potential in formulation optimisation. EFD experiments identified the least aggregation-prone molecule using a fraction of the material and time involved in traditional screening. We also show that the EFD can differentiate between different formulations and that protective formulations containing polysorbate 80 stabilised poorly developable Fc-fusion proteins against EFD-induced aggregation up to two-fold. Our work highlights common platform formulation additives that affect the extent of aggregation under EFD-stress, as well as identifying factors that modulate the underlying aggregation mechanism. Together, our data could aid the choice of platform formulations early in development for next-generation therapeutics including fusion proteins. [Display omitted]